On equivalence of infinitary formulas under the stable model semantics. Issue 1 (January 2015) - HARRISON, AMELIA; LIFSCHITZ, VLADIMIR; TRUSZCZYNSKI, MIROSLAW
Abstract Propositional formulas that are equivalent in intuitionistic logic, or in its extension known as the logic of here-and-there, have the same stable models. We extend this theorem to propositional formulas with infinitely long conjunctions and disjunctions and show how to apply this generalization to proving properties of aggregates in answer set programming.